Proyek Infografis Untuk Meningkatkan Kreativitas Siswa Dalam Pembelajaran Sejarah Daring - Hanna, Hanna; Santosa, Ayi Budi (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2024)
This Research is motivated by the findings of researchers in class XI IPS 1 SMAN 13 Bandung which shows the low creativity of students in history learning, where creativity is one of the important aspects that students need to have in participating in history learning. the findings that the researchers found in class XI IPS 1 SMAN 13 Bandung related to the low creativity of students during history learning who dared to be seen from the ability to think critically and innovatively of students in providing opinions, creative ideas as well as the low creativity of students involves in working on a project. This classroom action research was carried out in two cycles, in which three actions were carried out in each cycle using the Dave Ebbut mode, which in the process consisted of the stages of planning, implementation, observation, reconnaissance, and reflection. The purpose of this research is to increase students creativity in online history learning. the creativity indicator used as a guide in this study is Guilford’s opinion which consists of fluency, flexibility, elaboration, and originality, which the researcher develop into sub-indicators that have been adapted to the needs of the research. The scroe for each sub-indicator of the creativity indicators increased in each cycle so that from the score obtainde an increase in creativity was obtained from the first cycle with a percentage of 53% an increase of 33% in the second cycle with a percentage of 86%. This shows the success of implementating an effective infographic project to increase students creativity in online history learning.